Evaluación de tres extractos botánicos para el control de trips en el cultivo de rosas (rosas sp.), variedad (Mondial) en la parroquia la Esperanza, cantón Pedro Moncayo, provincia de Pichincha - Jarrín Sandoval, Ángel Fabián (2018)
VIII. SUMMARY The present investigation was conducted by Pedro Moncayo canton, province of Pichincha, located at the following geographic coordinates of, 0º 26'50,38 "north latitude and 78º 00'18.96" west longitude, with a height of 1,706 meters above sea level. To carry out the research, the Mondial rose variety was used in an established crop of 2 years of production under greenhouse conditions, taking into account the characteristics of the variety, the general objective was to evaluate the effect of the application of three botanical extracts organic (chili, garlic, barbasco) in rose cultivation (Rosa sp.) Mondial variety, in the control of thrips (Frankliniella occidentalis). We evaluated 8 treatments composed of Aji, Garlic, Barbasco, Aji-ajo, Aji-barbasco, Garlic-barbasco, Garlic-barbasco-aji and an absolute control, with three repetitions total 24 experimental units, the Block design was applied Completely Chance (DBCA). Determining that the application of garlic-barbasco-aji records greater pest control in the crop, with the lowest incidence of the trisp population after applications. It showed significant averages in button caliber and yield in quality stems per experimental unit and reached the highest economic profitability of $ 17,408.03 USD per hectare.